ASSESMENT OF QUALITY OF LIFE IN PATIENTS WITH ABUSE HEADACHE - Farrukh S. Saidvaliyev ,; Shakhnozakhon M. Rakhimova , (Central Asian Journal of Medicine, 2023)
In this study, various scales and questionnaires are used to assess quality of life and work productivity in patients with abuse headache, which are considered primary headaches. Even today, there are various theories regarding the origin and development of headache, however, the importance of migraine and tension headache as the primary headache in the development of abuse headache and more research is needed to determine its significance. In such cases, it is necessary to study the clinical and neurological features of abuse headache arising from primary headache.